The Influence of Leadership Behavior and Managerial Skills of School Principals on the Performance of Teachers at Jakarta School - Causirhom, Surya; Khiong, Khie; Nyanasuryanadi, Partono (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the impact of leadership behavior and managerial skills of school principals on teacher performance at Sekolah Ekayana Dharma Budhi Bakti Jakarta. In this study, a sample was consisting of all teachers in elementary, junior high, senior high, and vocational schools under the Sekolah Ekayana Dharma Budhi Bakti Jakarta, totaling 44 individuals. The data used in this research consists of primary data obtained through a structured questionnaire and secondary data obtained from relevant documents and academic records. Data were collected through a structured questionnaire designed to assess teachers' perceptions of the principal's leadership behavior, managerial skills, and their own performance. The analysis utilized multiple linear regression, conducted with SPSS version 26. The findings indicate that the principal's leadership behavior significantly influences teacher performance. Principals demonstrating strong leadership behavior enhance teachers' motivation and discipline, which positively impacts their performance. Additionally, the managerial skills of the principal contribute to teacher performance by fostering an effective resource management and problem-solving environment. Collectively, both leadership behavior and managerial skills create a motivating work atmosphere that improves teacher performance and job satisfaction.